Profil Psychological Wellbeing Remaja Di Pesantren - Santosa, Hardi; Meilani, Nurlia; Hartanto, Dody (JURNAL KONSELING GUSJIGANG, 2024)
Teenagers find it difficult to adapt when they first live in an Islamic boarding school, which results in their psychological well-being being disturbed. Psychological Wellbeing is an effort to overcome international challenges in saving adolescent psychology. However, this is inversely proportional to the psychological conditions that are quite worrying in today's teenagers. Including teenagers in Islamic boarding school environments, there is evidence of disturbances to the psychological health of teenagers in Islamic boarding school environments, there are behaviors such as anxiety and even depression in teenagers in Islamic boarding school environments. This research was conducted to determine the psychological well-being of junior high school students at the Wonosobo Islamic Boarding School using interview and survey methods. Based on the survey results, 58% had a medium level of psychological well-being, and 25% had a low level of psychological well-being. Low psychological well-being is a condition that must be considered.